Karakter dan Potensi Risiko Kerusakan Ekosistem Karst Cekungan Air Tanah Watuputih Kabupaten Rembang, Provinsi Jawa Tengah - Nandra Eko Nugroho; Wisnu Aji Dwi Kristanto (Jurnal Ilmiah Lingkungan Kebumian, 2019)
The research area is a burgeoning karst area which is part of the Kendeng Kars area in Rembang Regency, where the karstification process continues and has a complex subsurface system. In addition to the karst area of the Watuputih Groundwater Basin (CAT) written in Presidential Decree Number 26 of 2011 point 124 is included in the CAT B classification, which is located across the regency between Rembang and Blora Regencies. The morphological changes caused by human beings and the sharing of mining activities and plans for the construction of a cement factory by PT SI and its subsidiaries such as PT SG are also investors such as PT SIR, PT RSI, PT GMM, PT BA, PT RBP, PT SAF, PT ICCI which have reached an area 493 hectares in Tegaldowo, Gunem District. These activities will directly or indirectly damage the ecosystem of caves, underground rivers and parental springs that are scattered in the Watuputih CAT area. The Bengawan Solo River, the Lusi River and the Tuyuhan River are large rivers that tipped in the Watuputih CAT area. There are 74 caves, 29 springs, 44 ponors in the Tegaldowo and Timbrangan areas, 10 caves and 3 springs in the Perhutani area. Morphological changes due to mining can affect the pattern of water distribution, where caves, springs and ponors have a very important role in controlling water supply, the degradation of the amount of water stored in the Watuputih CAT results in changes in the composition of the base flow (diffuse flow) compared to the total flow. Limestone mining will reduce the absorption function and the amount of diffuse water storage, on the contrary will increase conduit flow when it rains. If an area has criteria as karst and CAT areas then it must be a major concern in the sustainability of its ecosystem. Provide protection and stop all activities that can damage geological protected areas that have karst landscapes and water recharge, especially from small scale or massive mining activities. Provides an understanding of karst areas in the perspective of disaster risk reduction. It needs to be developed and informed to various parties across sectors and across administrations so that appropriate policies can be made as an ecological function.Keywords: Watuputih Groundwater Basin, Water Distribution, Ecosystems, Ecological Function, Protection